Challenges faced by local municipalities in controlling the informal traders : the case of Polokwane Local Municipality - Selepe, M. (International Conference on Public Administration and Development Alternatives (IPADA), 2019)
The purpose of this paper is to unpack the challenges faced by local municipalities in controlling the forever increasing number of informal street traders and their unfriendly environmental practices. It is, however, cannot be argued that rapid growth of rural-urban migration and urbanisation phenomena together with a slow expansion of employment in the formal sector has forced the largest share of the workforce into the informal economy. Thus, placing much of the developmental burden on the government, local government in particular. Yet, it is also observed that, local municipalities throughout the country are going through a process of important, and often difficult change, and street trading accelerates as the local municipalities are also facing daily developmental problems. This paper also intends to find out any informal street traders measures that could be used by the municipalities in managing the sector as well as managing the uncontrollable influx of people who resorts to informal street trading in cities and towns. The study was conducted at the Polokwane Municipality. The study followed a qualitative approach, whereby personal interviews was conducted with the Polokwane Municipality's Local Economic Development office/unit to gather a sum of challenges experienced within the city posed by the informal street traders. The data in this paper is analysed and interpreted in a narrative form. Although, the findings and results are not limited to those collected from the municipality, the use of literature was employed to gather more information. Inter alia, the respondents indicated that there is a lack of enforcement of street trading by laws. The recommendations, amongst others, are that there should be law enforcement by the municipality, adherence to municipal by-laws by both the municipal officials and informal street traders, establishment of management structure, integrated management and planning, limiting overtrading and preference on trading levies.
The 4th Annual International Conference on Public Administration and Development Alternatives 03 - 05 July 2019, Southern Sun Hotel, OR Tambo International Airport, Johannesburg, South Africa
Keywords: Informal trading; Municipality; Polokwane; Development; Management; Informal sector (Economics); Small business -- South Africa; Municipal government -- South Africa -- Limpopo